Masking up for the benefit of others: exploring the link between individualistic/collectivistic cultural values and police officer propensity to obey COVID-19 rules off-duty - Kotlaja, Marijana (Policing during the COVID-19 pandemic, 2024)
Building on the idea of individualism and collectivism, this chapter explores the link between the values of the country’s dominant culture and police officers’ perceived compliance with COVID-19 rules. Our study utilizes the police officer surveys conducted in nine countries to assess the strength of the relationship between the country’s cultural context and the police officers’ expressed willingness to follow the COVID-19 rules. In particular, we study whether the police officers’ perceptions of other officers’ willingness to wear a mask off duty are connected in a systematic way to the dominant cultural values in the country. We find that the police officers’ mask-wearing behavior off duty is consistently but not statistically significantly related not only to the individual/collectivistic dimension of the Hofstede’s cultural measures, but also to the remaining five cultural dimensions.